Film distribution in Greece: formal and informal networks of circulation since the financial crisis. (19th December 2018) - Papadimitriou, Lydia
Abstract: The essay examines formal and informal film distribution in Greece since the financial crisis of 2009. By 'formal' I refer mainly to commercially organized theatrical, DVD and online distribution, while 'informal' consists of various networks of unlicensed circulation of films, usually referred to as 'piracy'. The essay's aims are threefold. As a media industries study, it focuses on formal distribution; it identifies the players that are involved in the process of rights acquisition and promotion of feature films in Greece, and explains their working practices. From a film studies perspective, it explores the mediating role of – both formal and informal – film distribution in helping (re)define and question the notion of national cinema. And finally, from a broader cultural studies angle, it presents a profile of the country in terms of which films are in circulation and how they are being watched, while pointing to comparisons with global and other national patterns of change. The essay positions Greece in the broader context of recent debates around contemporary film distribution and piracy, highlights methodological issues, and identifies the way in which global distribution practices manifest themselves locally in a specific 'small' territory of the European periphery.